2013
DOI: 10.1002/mawe.201300114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adsorbed magnetic and non‐magnetic atoms on electronic transport through surfaces with strong spin‐orbit coupling

Abstract: Adsorption‐induced reduction of the surface state conductivity in epitaxial Bi(111) films, a prototype system with a large Rashba‐induced surface state splitting by adsorbed atoms of Bi, Fe and Co was investigated by macroscopic surface magneto‐transport measurements at a temperature of 10 K. A detailed analysis of magneto‐transport, DC‐transport and Hall data reveals that the scattering efficiencies for Co and Fe are by a factor of two larger than for Bi. While for the latter, charge transfer and change of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although the transition into the semiconducting regime offers great potential for applications [20,21], it is still subject to an ongoing debate and the growing importance of surface states with increasing surface-to-volume ratio in very thin films has to be considered. The surface state conductivity of Bi(1 1 1) films has been found to be particularly large and in recent years various transport measurements [22][23][24][25][26][27][28], and magnetotransport measurements [29][30][31] suggested that the conductivity of thin films is composed of two channels, i.e. a semiconducting and a metallic contribution, ascribed to the film interior and surface.…”
Section: Introductionmentioning
confidence: 99%
“…Although the transition into the semiconducting regime offers great potential for applications [20,21], it is still subject to an ongoing debate and the growing importance of surface states with increasing surface-to-volume ratio in very thin films has to be considered. The surface state conductivity of Bi(1 1 1) films has been found to be particularly large and in recent years various transport measurements [22][23][24][25][26][27][28], and magnetotransport measurements [29][30][31] suggested that the conductivity of thin films is composed of two channels, i.e. a semiconducting and a metallic contribution, ascribed to the film interior and surface.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor-like behavior was confirmed by measurements of the temperature dependent conductivity, e.g., in Refs. [4][5][6][7][8][9]. The expected quantum confinement relies on the assumption that the crystal structure in the nanoscale system does not change considerably compared to the bulk and that there are no conducting surface states.…”
Section: Introductionmentioning
confidence: 99%